Teaching Material Development of Macromedia Flash 8.0-Based Production Écrite Pre Avancée - Tengku Ratna Soraya; Nurilam Harianja; Hesti Fibriasari (BIRCU, 2020)
Production Écrite Pre Avancée course is a course that aims to develop skills in working together and collaborating, adapting, being responsible, analyzing information and data, thinking critically and solving problems, creativity, communicating through writing, and using information and communication technology in learning activities on French writing at advanced level to achieve the students’ ability on writing complex French sentences that refer to the European standard curriculum (Cadre Européen Commun de Référence Pour Les Langues (CECRL) on Niveau B1 DELF. Teaching material development of Macromedia Flash 8.0-based Production Écrite Pre Avancée has a purpose for students to improve the writing ability on French text B1 level. This research makes teaching materials by using macromedia flash 8.0 software in Production Écrite Pre Avancée course. The research method used is Research and Development. The research is held at the French Language Study Program at FBS UNIMED by developing lecture teaching materials, to find out that these teaching materials can improve writing skills by French students Unimed.